2015
DOI: 10.1177/1756287215607418
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-invasive urothelial bladder cancer: an update on systemic therapy

Abstract: Urothelial carcinoma is a common malignancy that carries a poor prognosis when the disease includes muscle invasion. Metastatic urothelial carcinoma is almost uniformly fatal. The evidence behind treatment options in the neoadjuvant, adjuvant and metastatic settings are discussed in this manuscript, with a focused review of standard and investigational cytotoxic, targeted, and immunotherapy approaches. We have focused especially on neoadjuvant cisplatin-based therapy (supported by level one evidence) and on no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 124 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…Metastatic UC is almost uniformly fatal (1). However, progress in systemic therapies for muscle-invasive bladder carcinoma (MIBC) has been stagnant for decades, with few new systemic therapies being evaluated, until recently (2). Therefore, there is an urgent requirement for new potential therapeutic targets in UC.…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic UC is almost uniformly fatal (1). However, progress in systemic therapies for muscle-invasive bladder carcinoma (MIBC) has been stagnant for decades, with few new systemic therapies being evaluated, until recently (2). Therefore, there is an urgent requirement for new potential therapeutic targets in UC.…”
Section: Introductionmentioning
confidence: 99%
“…49 Additionally, the role of immune checkpoint inhibitors, such as PD-1 and PDL-1, is being actively explored in in phase I-III clinical trials in the neoadjuvant, adjuvant and metastatic settings. 50 Specifically, these inhibitors are hypothesized to prevent immune system tumor evasion and maximizing the body's immune response to malignant urothelial cells via regulation of T-cell activity. 50 Although no trials have been performed in the BPT setting, future studies may elucidate the role genetic or molecular markers in predicting response to BPT and the use of immunotherapy in this domain.…”
Section: Future Researchmentioning
confidence: 99%
“…While this holds promise particularly in tumor types that have established sensitivity to a given TT, its utility in mUC is purely investigational. Currently, no TTs are approved for use in patients with mUC, although several drugs and targets are being investigated in clinical trials [13,74]. The advantage of this strategy in tumors that are identified to have certain driver mutations for which a specific drug is available is compelling, as it theoretically allows for target-directed tumor cell killing with release of neoantigens followed by the capacity to generate a durable antitumor response.…”
Section: • Immunotherapymentioning
confidence: 99%
“…Despite this recommendation, retrospective studies in the USA and Europe have reported that the majority of patients do not ultimately receive this potentially life-preserving therapy [10][11][12]. Reasons cited for this have varied, but include concerns about the toxicities of chemotherapy leading to worsening performance status and treatment delays, ultimately contributing to worse perioperative outcomes, though many of these concerns have proved to be unfounded [12,13]. Fortunately, there is some evidence that practice patterns may be changing, increasing the proportion of MIBC patients offered NAC [11,14].…”
mentioning
confidence: 99%